THE IMPLEMENTATION OF THE INDONESIAN CURRICULUM IN ELEMENTARY SCHOOLS FOR THE 2022-2024 PERIOD - Aan Nurhasanah; Febby Fajar Nugraha; Mia Zultrianti Sari (Universitas Kuningan, 2024)
This study was conducted to determine how the implementation of the Merdeka Curriculum in elementary school driving schools. This study was conducted using a phenomenological approach because the researcher was interested in studying more deeply the phenomenon of implementing the Merdeka Curriculum in elementary schools, this study was also conducted to determine to what extent the implementation of the Merdeka Curriculum can be implemented in elementary schools. This study was conducted in several driving elementary schools in Kuningan Regency. The informants in this study were teachers, principals and facilitators. Data collection was carried out through in-depth interview techniques. As a basis for the interview instrument, the researcher used a guideline book for the stages of implementing the Merdeka Curriculum compiled by the BSKAP of the Ministry of Education, Culture, Research and Technology in 2022, which consists of 4 stages of implementing the Merdeka Curriculum, namely the initial stage, the developing stage, the ready stage, the advanced stage which consists of 14 aspects. Based on the 14 aspects observed in elementary schools. the results of information processing illustrate that there is 1 aspect, namely the design of the Operational Curriculum of the Education Unit (KOSP), the average school has reached the advanced stage, while the other 13 aspects, the average school is at the initial stage, namely the category still using the example/draft of the Merdeka Curriculum prepared by the Ministry of Education, Research and Technology in the independent teaching platform. Keywords: Implementation; Merdeka Curriculum; Elementary School